Designing for Digital Inclusion - Supporting Individuals with Cognitive Disability Through Digital Planning Tools - Jensen, Ebba; Pålsson, Edith (My University, 2025)
This thesis explores how a digital interface can improve support for individuals with cognitive disabilities in their participation at Daily Activity Centres (DACs), and how such support can promote equality, quality of life, and societal participation. DACs are part of Sweden’s LSS services and provide meaningful occupation for individuals unable to engage in paid employment. Despite these support structures, people with cognitive disabilities often face digital exclusion and limited participation in society. The project was carried out in collaboration with Välfärdsteknik Sverige, the developer of Boet, a digital planning tool originally designed for group homes and now being explored for use in DACs. To understand the specific context, challenges, and needs within DACs, observations and interviews were conducted with both staff and participants. These insights were synthesised into design goals and guidelines for creating a digital interface tailored to the DAC environment. Building on these findings, an iterative design process was carried out, resulting in a conceptual design for a web-based planning interface for staff. The design was evaluated in collaboration with DAC personnel to validate its relevance and usability. The results demonstrate how a digital planning tool, when grounded in user needs and used responsibly, can improve structured planning, individualised support, and digital inclusion at DACs. Ultimately, such tools have the potential to enhance autonomy and well-being as well as contribute to a more equal and inclusive society for individuals with cognitive disabilities.